2018
DOI: 10.1016/j.neuron.2018.06.035
|View full text |Cite
|
Sign up to set email alerts
|

The Innate Immune Receptors TLR2/4 Mediate Repeated Social Defeat Stress-Induced Social Avoidance through Prefrontal Microglial Activation

Abstract: Repeated environmental stress has been proposed to induce neural inflammation together with depression and anxiety. Innate immune receptors, such as Toll-like receptors (TLRs), are activated by exogenous or endogenous ligands to evoke inflammation. Here we show that the loss of TLR2 and TLR4 (TLR2/4) abolished repeated social defeat stress (R-SDS)-induced social avoidance and anxiety in mice. TLR2/4 deficiency mitigated R-SDS-induced neuronal response attenuation, dendritic atrophy, and microglial activation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
184
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 238 publications
(195 citation statements)
references
References 46 publications
9
184
1
1
Order By: Relevance
“…It has been reported that only mice lacking TLR2 and TLR4 in combination (TLR2/4 double knockout) abolished CSDS‐induced social avoidance. Neither TLR2 knockout nor TLR4 knockout alone could abolish CSDS‐induced social avoidance (Nie et al, ). Combined with our results, TLR4, in combination with TLR2, may participate in modulation of social avoidance, while TLR4 alone only modulates behavioral despair.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that only mice lacking TLR2 and TLR4 in combination (TLR2/4 double knockout) abolished CSDS‐induced social avoidance. Neither TLR2 knockout nor TLR4 knockout alone could abolish CSDS‐induced social avoidance (Nie et al, ). Combined with our results, TLR4, in combination with TLR2, may participate in modulation of social avoidance, while TLR4 alone only modulates behavioral despair.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study has found that voluntary exercise increases resilience to CSDS in mice (Mul et al, ), which indicates that voluntary exercise may be an effective and useful intervention to increase resilience to social defeat stress in humans. Gut microbiota, diet, and the immune system have also been implicated in resilience to CSDS in mice (Ambree, Ruland, Scheu, Arolt, & Alferink, ; Aubry et al, ; Kingston et al, ; McKim et al, ; Nie et al, ; Szyszkowicz, Wong, Anisman, Merali, & Audet, ). Improvement in eating habits may help change the immune system through alterations of microbiota, which may in turn increase resilience to social defeat stress in humans, especially given the strong correlations between the immune system and resilience to CSDS (Ambree et al, ; Aubry et al, ; McKim et al, ; Nie et al, ; Szyszkowicz et al, ).…”
Section: Social Status and Mtdmentioning
confidence: 99%
“…Gut microbiota, diet, and the immune system have also been implicated in resilience to CSDS in mice (Ambree, Ruland, Scheu, Arolt, & Alferink, ; Aubry et al, ; Kingston et al, ; McKim et al, ; Nie et al, ; Szyszkowicz, Wong, Anisman, Merali, & Audet, ). Improvement in eating habits may help change the immune system through alterations of microbiota, which may in turn increase resilience to social defeat stress in humans, especially given the strong correlations between the immune system and resilience to CSDS (Ambree et al, ; Aubry et al, ; McKim et al, ; Nie et al, ; Szyszkowicz et al, ). tDCS is a noninvasive intervention that has already been applied for the treatment of depression in clinical practice (Fregni et al, ; Nitsche, Boggio, Fregni, & Pascual‐Leone, ).…”
Section: Social Status and Mtdmentioning
confidence: 99%
“…1 Animal studies using a variety of stress models such as social defeat stress, chronic mild stress, and restraint stress in rodents have revealed that exposure to environmental stress induces inflammatory responses in the brain and systemic circulation, thereby contributing to emotional alternations. [2][3][4][5][6] For example, social defeat stress activates microglia in several brain areas including the medial prefrontal cortex, and this activation is indispensable for dendritic atrophy in the medial prefrontal cortex and the induction of social avoidance. 2 Social defeat stress also induces the production of interleukin-6 in bone marrow-derived leukocytes.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6] For example, social defeat stress activates microglia in several brain areas including the medial prefrontal cortex, and this activation is indispensable for dendritic atrophy in the medial prefrontal cortex and the induction of social avoidance. 2 Social defeat stress also induces the production of interleukin-6 in bone marrow-derived leukocytes. 7 The circulating IL-6 has been shown to enter the brain parenchyma due to concomitant disruption of the blood-brain barrier for the induction of social avoidance.…”
Section: Introductionmentioning
confidence: 99%